Employee Digital Competency Development Strategy at The BKPSDM of Gunungsitoli City - Laoli, Febi Plantiani; Lase, Delipiter; Zega, Yamolala; Telaumbanua, Eliagus (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study analyzes strategies for developing employees’ digital competence at the Human Resources Development Agency (BKPSDM) of Gunungsitoli City. Using a qualitative descriptive method, the research explores employees’ digital competence levels, training needs, supporting and inhibiting factors, and the impact of development strategies on personnel service performance. Data were collected through interviews, observations, and documentation involving key informants and supporting staff. The findings reveal that the overall digital competence of employees is at an adequate level, supported by an online recruitment system that filters candidates with basic digital skills. However, variations in digital ability across employees highlight the need for continuous development through structured, medium- to long-term training such as formal education and integrated digital learning. Key strategies identified include integrating digital applications to enhance efficiency, fostering a culture of innovation through knowledge sharing and open communication, and strengthening collaboration with the Communication and Information Agency and educational institutions. These efforts contribute to improving service quality, transparency, and efficiency in public administration. The study emphasizes that sustainable digital competence development is essential for enhancing organizational performance and achieving better public service outcomes in the digital era.